Data for paper "Improving the Flexibility and Robustness of Model-Based Derivative-Free Optimization Solvers" - Roberts, L; Cartis, C (University of Oxford, 2019)
This is the raw data for paper "Improving the Flexibility and Robustness of Model-Based Derivative-Free Optimization Solvers" - details can be found in the paper and the dataset README file.